Nickel-based precipitation hardenable alloys with improved hydrogen embrittlement resistance

By adjusting the composition and heat treatment process of nickel-based precipitable hardened alloy, the titanium content is reduced and the iron content is increased, the problem of insufficient hydrogen embrittlement resistance in the oil field environment is solved, and the high yield strength and hydrogen embrittlement resistance are improved.

CN119213151APending Publication Date: 2024-12-27HUNTINGTON ALLOYS CORP (US)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202280091133.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2021-12-30
Filing Date
2022-12-30
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Nickel-based precipitable hardened alloys have insufficient resistance to hydrogen-induced stress corrosion cracking (HE) in oil field environments, making it difficult to meet the needs of improving hydrogen embrittlement resistance.

Method used

By adjusting the composition of the alloy, reducing the titanium (Ti) content and increasing the iron (Fe) content, combined with a specific heat treatment process, a new nickel-based precipitable hardened alloy was developed, which improves its plastic strain ratio and failed plastic strain, and enhances hydrogen resistance. brittleness.

Benefits of technology

The high yield strength of the alloy and the improvement of hydrogen embrittlement resistance are achieved, which meets the requirements of hydrogen corrosion resistance of downhole components of oilfield equipment, and reduces the positive contribution of titanium content to hydrogen embrittlement resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004981977590000041
    Figure BDA0004981977590000041
  • Figure BDA0004981977590000051
    Figure BDA0004981977590000051
  • Figure BDA0004981977590000052
    Figure BDA0004981977590000052
Patent Text Reader

Abstract

Nickel-based precipitation hardenable alloys with enhanced hydrogen embrittlement resistance and desired yield strength have, inter alia, critical ranges of titanium and iron elements. A nickel-based precipitation hardenable alloy has a composition, in wt%, from about 18.0% to about 23.0% Cr, from about 7.0% to about 12.0% Fe, from about 6.5% to about 9.5% Mo, from about 3.2% to about 5.2% Nb, from about 0.3% to about 1.3% Ti, up to about 0.4% Al, and the balance Ni and unavoidable impurities. The alloy has a yield strength (0.2% residual deformation) of greater than or equal to 120 ksi (827 MPa), a plastic strain ratio of greater than or equal to 0.35, and a failure plastic strain of greater than or equal to 9.0%.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority to and the benefit of U.S. Patent Application No. 63 / 295,324, filed on December 30, 2021. The disclosure of the above application is hereby incorporated herein by reference. Technical Field

[0003] The present disclosure relates to a nickel-based precipitation hardenable alloy, and more particularly to a nickel-based precipitation hardenable alloy having improved hydrogen embrittlement resistance. Background Art

[0004] The statements in this section merely provide background information related to the present disclosure and may not constitute prior art.

[0005] Nickel-based precipitation hardenable alloys are used to manufacture key downhole components in oilfield equipment. This alloy is known to resist chloride ion stress corrosion cracking, sulfide stress corrosion cracking and electroplating-induced hydrogen stress corrosion cracking. However, increasing hydrogen embrittlement resistance (HE) is desirable. Hydrogen embrittlement resistance can be evaluated by measuring plastic strain ratio and failure plastic strain. As used herein, phrases "failure plastic strain (plastic strain to failure)" and "plastic strain ratio (plastic strain ratio)" refer to failure plastic strain and plastic strain ratio established in NACE Standard TM0198. The standard provides a slow strain rate test for evaluating the resistance of Ni-based alloys to hydrogen-induced stress corrosion cracking (SCC) at elevated temperatures in simulated oilfield production environments. More specifically, failure plastic strain is the maximum plastic deformation of the material before the material breaks. The projection of the elastic line of the stress and strain values ​​at the time of failure is used to determine the strain amount attributed to the plastic deformation of the sample, as the total strain at the time of failure minus the equivalent elastic strain at the failure point. The HE plastic strain ratio is the plastic strain at failure determined from samples tested in acid divided by the plastic strain at failure determined from samples tested in an inert environment.

[0006] The present disclosure addresses the problem of improved HE resistance of nickel-based precipitation hardenable alloys and other problems associated with nickel-based precipitation hardenable alloys used in oilfield environments. Summary of the invention

[0007] This section provides a general summary of the disclosure, and is not a comprehensive disclosure of its full scope or all of its features.

[0008] In one form of the present disclosure, a Ni-based precipitation hardenable alloy has a composition, in wt%, of about 18.0% to about 23.0% Cr, about 7.0% to about 12.0% Fe, about 6.5% to about 9.5% Mo, about 3.2% to about 5.2% Nb, about 0.3% to about 1.3% Ti, up to about 0.4% Al, and the balance is Ni and unavoidable impurities, a yield strength greater than or equal to 120 ksi, a plastic strain ratio greater than 0.35, and a failure plastic strain greater than or equal to 9.0%. In at least one variation, the alloy has a Ti content of about 0.8% to about 1.1% and an Fe content of about 9.0% to about 12.0%. For example, in at least one variation, the alloy has a Ti content of about 0.8% to about 1.0% and an Fe content of about 10.0% to about 12.0%. In another alternative, the alloy has a Ti content of about 0.4% to about 0.8% and a Fe content of about 10.0% to about 12.0%.

[0009] Although one form of the alloy has a desired plastic strain ratio, i.e., greater than or equal to 0.35, and a failure plastic strain of greater than or equal to 9.0%, the alloy also maintains a desired strength, i.e., greater than or equal to 120 ksi (827 MPa). For example, in at least one variation, the alloy has a HE plastic strain ratio greater than or equal to 0.35, a failure plastic strain greater than 9.0%, and a yield strength between about 120 ksi (827 MPa) and 150 ksi (1034 MPa). In addition, in some variations, the alloy has a plastic strain ratio greater than or equal to 0.40 and a failure plastic strain greater than or equal to 10.0%. For example, in at least one variation, the plastic strain ratio is greater than or equal to 0.50 and the failure plastic strain is greater than or equal to 12.0%.

[0010] In another form of the present disclosure, a Ni-based precipitation hardenable alloy has a composition, in wt%, of about 18.0% to about 23.0% Cr, about 9.0% to about 16.0% Fe, about 4.5% to about 7.5% Mo, about 3.2% to about 5.2% Nb, about 0.4% to about 1.3% Ti, up to about 0.4% Al, and the balance is Ni and unavoidable impurities, a yield strength greater than or equal to 120 ksi, a plastic strain ratio greater than or equal to 0.30, and a failure plastic strain greater than or equal to 8.5%. In at least one variation, the alloy has a Ti content of about 0.8% to about 1.1% and an Fe content of about 11.0% to about 16.0%. For example, in at least one variation, the alloy has a Ti content of about 0.8% to about 1.0% and an Fe content of about 12.0% to about 16.0%. In another alternative, the alloy has a Ti content of about 0.5% to about 0.8% and a Fe content of about 12.0% to about 16.0%.

[0011] Although this form of the alloy has a desired plastic strain ratio, i.e., greater than or equal to 0.30, the alloy still maintains a desired strength, i.e., greater than or equal to 120 ksi (827 MPa). For example, at least one modified alloy has a plastic strain ratio greater than or equal to 0.30, a failure plastic strain greater than or equal to 8.5%, and a yield strength between about 120 ksi (827 MPa) and 150 ksi (1034 MPa). In addition, in another form, the alloy has a plastic strain ratio greater than or equal to 0.35 and a failure plastic strain greater than or equal to 9.0%. In yet another form, the plastic strain ratio is greater than or equal to 0.45, and the failure plastic strain is greater than or equal to 10.0%.

[0012] In yet another form of the present disclosure, a Ni-based precipitation hardenable alloy has the following composition, in wt%, about 18.0% to about 23.0% Cr, about 15.0% to about 21.0% Fe, about 3.0% to about 4.5% Mo, about 3.2% to about 5.2% Nb, about 0.5% to about 1.3% Ti, up to about 0.4% Al, about 0.5% to about 3.0% Cu, and the balance is Ni and unavoidable impurities. The alloy has a yield strength greater than or equal to 140 ksi, a plastic strain ratio greater than or equal to 0.30, and a failure plastic strain greater than or equal to 8.0%. In at least one variation of the alloy, the Ti content is about 0.8% to about 1.1%, and the Fe content is about 16.0% to about 21.0%. For example, in at least one variation, the alloy has a Ti content of about 0.8% to about 1.0% and a Fe content of about 17.0% to about 20.0%. In another alternative, the alloy has a Ti content of about 0.5% to about 0.8% and a Fe content of about 18.0% to about 21.0%.

[0013] Although the alloy has a desired plastic strain ratio, i.e., greater than or equal to 0.5, the alloy still maintains a desired strength, i.e., greater than or equal to 140 ksi (965 MPa). For example, in at least one variation, the alloy has a plastic strain ratio greater than or equal to 0.30, a failure plastic strain greater than or equal to 8.0%, and a yield strength between about 140 ksi (965 MPa) and 170 ksi (1172 MPa). In addition, in some variations, the alloy has a plastic strain ratio greater than or equal to 0.35 and a failure plastic strain greater than or equal to 9.0%. In yet another form, the plastic strain ratio is greater than or equal to 0.45, and the failure plastic strain is greater than or equal to 10.0%.

[0014] While not being bound by any particular theory, it is believed that a careful balance of Ti and Fe results in the alloy providing high strength and resistance to hydrogen embrittlement.

[0015] Further areas of applicability will become apparent from the description provided herein.It should be understood that the description and specific examples are intended for purposes of illustration only and are not intended to limit the scope of the present disclosure. DETAILED DESCRIPTION

[0016] The following description is merely exemplary in nature and is not intended to limit the present disclosure, application, or uses. It should be understood that throughout the drawings, corresponding reference numerals indicate the same or corresponding parts and features.

[0017] Referring to Table 1 below, the Unified Numbering System (UNS) composition specifications for nine (9) nickel-based (Ni-based) precipitation-hardenable alloys are shown.

[0018]

[0019]

[0020] Table 1

[0021] The alloys shown in Table 1 are known for use in a variety of industries and applications, some of which include downhole components in oilfield equipment, and are expected to have improved HE resistance. Alloys falling within the UNS specifications shown in Table 1 were subjected to HE testing (see Paper No. 13284, CORROSION 2019 Conference Proceedings; incorporated herein by reference). In addition, the inventors conducted a statistical analysis of the composition of the alloys in Table 1 and found that the HE resistance of these alloys showed a trend of improved HE resistance, which was a function of reducing the Ti content and increasing the Fe content. In particular, based on statistical modeling, it was found that the plastic strain ratio of the alloys obeyed the following relationship:

[0022] Plastic strain ratio = 0.3461 + 0.016572 * Fe - 0.2022 * Ti (1)

[0023] The determination coefficient (R 2 ) is equal to 0.997, and Fe and Ti are expressed in weight percentage (wt%). From the above relationship (1), it can be seen that by reducing the Ti content and increasing the Fe content, the plastic strain ratio increases and the HE resistance is improved.

[0024] Referring now to Table 2, four Ni-based alloys having varying amounts of chromium, iron, molybdenum, niobium, titanium, and aluminum are shown. In particular, specific alloys that generally fall within the composition ranges of UNS N07716, UNS N07718, UNS N09925, and UNS N09945 are shown in Table 2. It should be understood that the compositions of the alloys shown in Table 2 were obtained from Paper No. 4248, CORROSION 2014 Conference Proceedings (incorporated herein by reference), and may not include all of the alloying elements in the UNS specifications listed in the table.

[0025]

[0026]

[0027] Table 2

[0028] The alloys in Table 2 were subjected to HE testing (see Paper 4248, CORROSION 2014 Conference Proceedings). Likewise, statistical analysis of the alloy compositions in Table 2 and the HE resistance of these alloys similarly showed a trend of enhanced HE resistance as a function of decreasing Ti content and increasing Fe content. In particular, it was found that the reduction in the area ratio of testing in a HE environment to testing in an inert environment obeys the following relationship based on statistical modeling:

[0029] Area reduction rate = 0.6348 + 0.01274 * Fe - 0.1530 * Ti (2)

[0030] Where R 2 Equal to 0.779.

[0031] Referring now to Table 3, seven (7) Ni-based precipitation hardenable alloys are shown having varying amounts of chromium, iron, molybdenum, niobium, titanium, and aluminum. In particular, specific alloys that generally fall within the composition ranges of UNS N07725, UNS N07716, and UNS N07718 are shown in Table 3. It should be understood that the compositions of the alloys shown in Table 3 were obtained from Paper No. 11114, CORROSION 2018 Conference Proceedings (incorporated herein by reference), and may not include all of the alloying elements provided in the corresponding UNS specifications.

[0032]

[0033]

[0034] Table 3

[0035] The alloys in Table 3 were subjected to HE testing (see Paper 11114, 2018 Conference Proceedings). Likewise, statistical analysis of the alloy compositions in Table 3 and the HE resistance of these alloys similarly showed a trend of enhanced HE resistance as a function of decreasing Ti content. In particular, the reduction in fracture load for alloys tested in a HE environment versus those tested in an inert environment was found to follow a relationship based on statistical modeling:

[0036] Fracture load reduction % = -43.4 + 52.24 * Ti (3)

[0037] R 2= 0.876, higher values ​​of fracture load reduction (ie less negative values) indicate higher HE resistance. As shown in relation (3), for the alloys shown in Table 3, the contribution of Fe is not statistically correlated with the % fracture load reduction.

[0038] It should be appreciated that the analytical results show that as the Ti alloying content in the Ni-based precipitation hardenable alloy decreases, HE resistance increases. Therefore, according to the teachings herein, a new Ni-based precipitation hardenable alloy having a reduced Ti content and increased Fe and increased HE resistance has been developed.

[0039] Further testing was conducted to further develop the effects of Ti, Fe and yield strength (YS) on HE resistance of precipitation hardenable nickel alloys. Referring now to Table 4 below, the compositions of the nickel-based (Ni-based) precipitation hardenable alloys tested are shown. Combinations of commercial and laboratory alloys are included.

[0040]

[0041]

[0042]

[0043]

[0044] Table 4

[0045] The laboratory melt alloys in Table 4 were made from 4 inch diameter, 50 pound vacuum induction (VIM) melted ingots in the form of hot rolled bar products with a diameter of 0.625". The homogenized and hot rolled bar samples were annealed at 1900°F. Age hardening was performed at 1350°F for 8 hours, furnace cooled 100°F / hour to 1150°F, held for 8 hours, and then air cooled. The production melt alloys were made from commercial VIM melt material. 18" diameter VIM electrodes were vacuum arc remelted (VAR) to 20" diameter and forged using a rotary forging machine (GFM) to a final diameter of 5 to 10" diameter. As shown in Table 5 below, the finished bars were annealed between 1850-1900°F. Age hardening was performed between 1300-1365°F for 5.5-8 hours, furnace cooled 50-100°F / hour to 1150°F, held for 5.5-12 hours, and then air cooled.

[0046]

[0047]

[0048] Table 5

[0049] Tensile strength and Charpy impact tests were performed on the alloys in Table 5. The test results for each heat are summarized in Table 6 below:

[0050]

[0051]

[0052] Table 6

[0053] The alloys in Table 5 were further tested for HE resistance. Each variant was tested for HE resistance by the NACE TM0198 Method C slow strain rate test method. The slow strain rate test involves slow dynamic strain applied at a constant extension rate. It evaluates resistance to hydrogen-induced stress cracking. Table 7 summarizes the average test results for HE resistance at each heat. (Blank or no value indicates that the alloy was not tested).

[0054]

[0055]

[0056] Table 7

[0057] All samples were examined by optical microscopy to confirm that the microstructure met the requirements defined in API6A CRA Annex A, Reference Microstructure, and that there were no significant grain boundary or intragranular precipitation. It has been shown that such microstructures are susceptible to intergranular fracture under HE conditions. Such microstructures were excluded from the current study to isolate the effects of Ti and Fe and yield strength on HE properties without the additional effect of significant grain boundary precipitation.

[0058] Through data analysis and cross-validation including univariate and multivariate regression models, it was determined that Ti content, Fe content and yield strength each have an effect on HE resistance. In particular, in the yield strength range of 120-170 ksi, lower Ti content and higher Fe content correspond to increased HE resistance.

[0059] The test results were evaluated and used to guide the scope of the claims contained herein. Table 8 below shows a summary of the composition ranges, plastic strain ratios, and yield strengths of new alloys according to the present disclosure.

[0060]

[0061]

[0062] Table 8

[0063] In one form of the present disclosure, as shown in Table 8 as "A-New Alloy 725", a Ni-based precipitation hardenable alloy has a composition, in wt%, of about 18.0% to about 23.0% Cr, about 7.0% to about 12.0% Fe, about 6.5% to about 9.5% Mo, about 3.2% to about 5.2% Nb, about 0.3% to about 1.3% Ti, up to about 0.4% Al, and the balance being Ni and unavoidable impurities, a plastic strain ratio of greater than or equal to 0.35, or a failure plastic strain of greater than or equal to 9.0%. In some variations, the alloy has a Ti content between about 0.8% and about 1.1%, while in other variations, the alloy has a Ti content between about 0.8% and about 1.0%. In at least one variation, the alloy has a Ti content of about 0.8% to about 1.1% and a Fe content of about 9.0% to about 12.0%. For example, in at least one variation, the alloy has a Ti content of about 0.8% to about 1.0% and an Fe content of about 10.0% to about 12.0%. In addition, additional alloying elements such as B, C, Co, Mn, P, Si, and S may be present in amounts corresponding to the UNS N07725 specification and / or normal melting practices for making Ni-based precipitation hardenable alloys while remaining within the scope of the present disclosure.

[0064] Although the alloy has a desired plastic strain ratio, i.e., greater than or equal to 0.35, the alloy also maintains a desired strength, i.e., greater than or equal to 120 ksi (827 MPa). That is, even if Ti is reduced to a lower level within or below the Ti range for UNS N07725, the alloy still has the yield strength required for downhole components in oil field production. For example, in at least one variation, the alloy has a plastic strain ratio greater than or equal to 0.35, and the yield strength is between about 120 ksi (827 MPa) and 150 ksi (1034 MPa). In one form, the alloy has a plastic strain ratio greater than or equal to 0.3, and the yield strength is between about 130 ksi (896 MPa) and 150 ksi (1034 MPa). In another form, the alloy has a plastic strain ratio greater than or equal to 0.35, a plastic strain ratio greater than or equal to 9.0%, and a yield strength between about 140 ksi (965 MPa) and 150 ksi (1034 MPa). In addition, in some variations, the alloy has a plastic strain ratio greater than or equal to 0.40 and a failure plastic strain greater than or equal to 10.0%. For example, in at least one variation, the plastic strain ratio is greater than or equal to 0.50 and the failure plastic strain is greater than or equal to 12.0%.

[0065] In another form of the present disclosure, represented by B-New Alloy 735 in Table 8, a Ni-based precipitation hardenable alloy has a composition, in wt%, of about 18.0% to about 23.0% Cr, about 9.0% to about 16.0% Fe, about 4.5% to about 7.5% Mo, about 3.2% to about 5.2% Nb, about 0.4% to about 1.3% Ti, up to about 0.4% Al, and the balance being Ni and unavoidable impurities, a plastic strain ratio greater than or equal to 0.3, or a failure plastic strain greater than or equal to 8.5%. In one form, the alloy has a Ti content between about 0.8% and about 1.1%, while in other variations, the alloy has a Ti content between about 0.8% and about 1.0%. In at least one variation, the alloy has a Ti content of about 0.8% to about 1.1% and a Fe content of about 14.0% to about 17.0%. In another form, the alloy has a Ti content of about 0.8% to about 1.0% and an Fe content of about 15.0% to about 17.0%. In addition, additional alloying elements such as B, C, Co, Mn, P, Si and S may be present in amounts corresponding to normal melting practices for making Ni-based precipitation hardenable alloys while remaining within the scope of the present disclosure.

[0066] Although the alloy has a desired plastic strain ratio, i.e., greater than or equal to 0.30, the alloy still maintains a desired strength, i.e., greater than or equal to 120 ksi (827 MPa). For example, in at least one variation, the alloy has a plastic strain ratio greater than or equal to 0.30, a failure plastic strain greater than or equal to 8.5%, and a yield strength between about 120 ksi (827 MPa) and 150 ksi (1034 MPa). In one form, the alloy has a plastic strain ratio greater than or equal to 0.30, a failure plastic strain greater than or equal to 8.5%, and a yield strength between about 130 ksi (896 MPa) and 150 ksi (1034 MPa). In yet another form, the alloy has a plastic strain ratio greater than or equal to 0.30, a failure plastic strain greater than or equal to 8.5%, and a yield strength between about 140 ksi (965 MPa) and 150 ksi (1034 MPa). In another form, the alloy has a HE plastic strain ratio greater than or equal to 0.35 and a failure plastic strain greater than or equal to 9.0%. In yet another form, the plastic strain ratio is greater than or equal to 0.45 and the failure plastic strain is greater than or equal to 10.0%.

[0067] In yet another form of the present disclosure corresponding to C-New Alloy 945X in Table 8, the Ni-based precipitation hardenable alloy has the following composition, in wt%, about 18.0% to about 23.0% Cr, about 15.0% to about 21.0% Fe, about 3.0% to about 4.5% Mo, about 3.2% to about 5.2% Nb, about 0.5% to about 1.3% Ti, up to about 0.4% Al, about 0.5% to about 3.0% Cu, and the balance is Ni and unavoidable impurities, a plastic strain ratio greater than or equal to 0.3, or a failure plastic strain greater than or equal to 8.0%. In one form, the alloy has a Ti content between about 0.8% and about 1.1%, while in other forms, the alloy has a Ti content between about 0.8% and about 1.0%. In at least one variation, the alloy has a Ti content of about 0.8% to about 1.1% and an Fe content of about 19.0% to about 22.0%. In yet another form, the alloy has a Ti content of about 0.8% to about 1.0% and an Fe content of about 20.0% to about 22.0%. In addition, additional alloying elements such as B, C, Co, Mn, P, Si, and S may be present in amounts corresponding to the UNSN 09946 specification and / or normal melting practices for making Ni-based precipitation hardenable alloys while remaining within the scope of the present disclosure.

[0068] Despite the alloy having a desired plastic strain ratio, i.e., greater than or equal to 0.3, the alloy still maintains a desired strength, i.e., greater than or equal to 140 ksi (965 MPa). For example, in at least one variation, the alloy has a plastic strain ratio greater than or equal to 0.30, a failure plastic strain greater than or equal to 8.0%, and a yield strength between about 140 ksi (965 MPa) and 170 ksi (1172 MPa). In one form, the alloy has a plastic strain ratio greater than or equal to 0.30, a failure plastic strain greater than or equal to 8.0%, and a yield strength between about 145 ksi and 170 ksi (1172 MPa). In another form, the alloy has a plastic strain ratio greater than or equal to 0.30, a failure plastic strain greater than or equal to 8.0%, and a yield strength between about 150 ksi (1034 MPa) and 170 ksi (1172 MPa). In yet another form, the alloy has a plastic strain ratio greater than or equal to 0.35 and a plastic strain to failure greater than or equal to 9.0%. In another form, the plastic strain ratio is greater than or equal to 0.45 and the plastic strain to failure is greater than or equal to 10.0%.

[0069] It should be understood from the disclosed compositions, HE resistance measures (i.e., failure plastic strain or plastic strain ratio) and strength (i.e., yield strength) of the above-described new alloys according to the present disclosure that a critical range of Ti is required. That is, it has been found that the critical range of Ti in the alloy is such that the desired HE resistance is provided or exceeded while providing or exceeding the desired yield strength level. In particular, for Ti contents less than the minimum value shown in Table 8 above, the alloy has an undesirable (e.g., low) yield strength, while for Ti contents greater than the maximum value shown in Table 8, the alloy has an undesirable (e.g., low) HE resistance. In some variations of the present disclosure, a critical range of Ti and a critical range of Fe are ideal. That is, it has been found that the critical range of Ti and the critical range of Fe in the alloy are such that the desired HE resistance is provided or exceeded, the desired yield strength level is provided or exceeded, and alloying elements such as Mo and Cr are generally maintained in solid solution, i.e., there are no undesirable Mo-rich and / or Cr precipitates (e.g., σ phase) in the new alloy. In at least one variation of the present disclosure, there is a synergistic effect between Ti and Fe that provides a combination of high HE resistance, desirable yield strength, and desirable microstructure with reduced or no undesirable Mo- and / or Cr-rich precipitates.

[0070] It should also be understood that the alloy compositions shown in Table 8 include all incremental values ​​between the minimum alloying element composition and the maximum alloying element composition listed above. That is, the minimum alloying element composition value of any alloy shown in Table 8 can be within the range of the minimum value to the maximum value shown in the table. Similarly, the maximum alloying element composition value of any alloy shown in Table 8 can be within the range of the maximum value to the minimum value shown in the table. For example, the minimum Ti content of A-New Alloy 725 can be 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2 or 1.3, and any value between these incremental values, and the maximum Ti content of A-New Alloy 725 can be 1.3, 1.2, 1.1, 1.0, 0.9, 0.8, 0.7, 0.6, 0.5, 0.4 or 0.3, and any value between these incremental values.

[0071] Similarly, the yield strengths of the alloys shown in Table 8 include all incremental values ​​between the minimum yield strength values ​​and the maximum yield strength values ​​listed above. That is, the minimum yield strength value of any alloy shown in Table 8 may be within the range of the minimum yield strength value to the maximum yield strength value shown in the table. Likewise, the maximum yield strength value of any alloy shown in Table 8 may be within the range of the maximum yield strength value shown in the table to the minimum yield strength value shown in the table.

[0072] Similarly, the plastic strain ratios of the alloys shown in Table 8 include all incremental values ​​between the minimum plastic strain ratio and the maximum plastic strain ratio described above. That is, the minimum plastic strain ratio value of any alloy shown in Table 8 may be within the range of the minimum plastic strain ratio value to the maximum plastic strain ratio value shown in the table.

[0073] Similarly, the HE plastic strains of the alloys shown in Table 8 include all incremental values ​​between the above-mentioned minimum failure plastic strain and the maximum failure plastic strain. That is, the minimum plastic strain value of any alloy shown in Table 8 may be within the range of the minimum plastic strain value to the maximum plastic strain value shown in the table.

[0074] Unless otherwise expressly stated, in describing the scope of the present disclosure, all numerical values ​​expressing mechanical / thermal properties, composition percentages, dimensions and / or tolerances or other properties should be understood to be modified by the word "about" or "approximately". Such modifications are required for various reasons including industrial practice, manufacturing techniques and testing capabilities.

[0075] As used herein, the phrase at least one of A, B, and C should be construed to mean a logical (A OR B OR C), using a non-exclusive logical OR, and should not be construed to mean "at least one of A, at least one of B, and at least one of C."

[0076] The description of the present disclosure is merely exemplary in nature, and therefore, variations that do not depart from the essence of the present disclosure are intended to be within the scope of the present disclosure. These variations should not be regarded as departing from the spirit and scope of the present disclosure.

Claims

1. A nickel-based precipitation hardenable alloy comprising: The composition, in weight percent, comprises: about 18.0% to about 23.0% chromium; from about 7.0% to about 12.0% iron; about 6.5% to about 9.5% molybdenum; from about 3.2% to about 5.2% niobium; from about 0.3% to about 1.3% titanium; Up to about 0.4% aluminum; and The balance is nickel and unavoidable impurities; wherein the nickel-based precipitation hardenable alloy has: A yield strength (0.2% residual strain) of greater than or equal to about 120 ksi (827 MPa); A plastic strain ratio greater than or equal to 0.35; and Failure plastic strain greater than or equal to 9.0%.

2. The nickel-based precipitation hardenable alloy according to claim 1, wherein: The titanium is between about 0.8% and about 1.1%, and the iron is between about 9.0% and about 12.0%.

3. The nickel-based precipitation hardenable alloy according to claim 1, wherein: The titanium is between about 0.8% and about 1.0%, and the iron is between about 10.0% and about 12.0%.

4. The nickel-based precipitation hardenable alloy according to claim 1, wherein: The titanium is between about 0.4% and about 0.8%, and the iron is between about 10.0% and about 12.0%.

5. The nickel-based precipitation hardenable alloy according to claim 1, wherein: The yield strength (0.2% residual strain) is between about 120 ksi (827 MPa) and 150 ksi (1034 MPa).

6. The nickel-based precipitation hardenable alloy according to claim 1, wherein: The plastic strain ratio is greater than or equal to 0.40, and the failure plastic strain is greater than or equal to 10.0%.

7. The nickel-based precipitation hardenable alloy according to claim 1, wherein: The plastic strain ratio is greater than or equal to 0.50, and the failure plastic strain is greater than or equal to 12.0%.

8. A nickel-based precipitation hardenable alloy comprising: The composition, in weight percent, comprises: about 18.0% to about 23.0% chromium; from about 9.0% to about 16.0% iron; about 4.5% to about 7.5% molybdenum; from about 3.2% to about 5.2% niobium; about 0.4% to about 1.3% titanium; Up to about 0.4% aluminum; and The balance is nickel and unavoidable impurities; wherein the nickel-based precipitation hardenable alloy has: A yield strength (0.2% residual strain) of greater than or equal to about 120 ksi (827 MPa); A plastic strain ratio greater than or equal to 0.30; and Failure plastic strain greater than or equal to 8.5%.

9. The nickel-based precipitation hardenable alloy according to claim 8, wherein: The titanium is between about 0.8% and about 1.1%, and the iron is between about 11.0% and about 16.0%.

10. The nickel-based precipitation hardenable alloy according to claim 8, wherein: The titanium is between about 0.8% and about 1.0%, and the iron is between about 12.0% and about 16.0%.

11. The nickel-based precipitation hardenable alloy according to claim 8, wherein: The titanium is between about 0.5% and about 0.8%, and the iron is between about 12.0% and about 16.0%.

12. The nickel-based precipitation hardenable alloy according to claim 8, wherein: The yield strength (0.2% residual strain) is between about 120 ksi (827 MPa) and 150 ksi (1034 MPa).

13. The nickel-based precipitation hardenable alloy according to claim 8, wherein: The plastic strain ratio is greater than or equal to 0.35, and the failure plastic strain is greater than or equal to 9.0%.

14. The nickel-based precipitation hardenable alloy according to claim 8, wherein: The plastic strain ratio is greater than or equal to 0.45, and the failure plastic strain is greater than or equal to 10.0%.

15. A nickel-based precipitation hardenable alloy comprising: The composition, in weight percent, comprises: about 18.0% to about 23.0% chromium; from about 15.0% to about 21.0% iron; about 3.0% to about 4.5% molybdenum; from about 3.2% to about 5.2% niobium; about 0.5% to about 1.3% titanium; up to about 0.4% aluminum; from about 0.5% to about 3.0% copper; and The balance is nickel and unavoidable impurities; wherein the nickel-based precipitation hardenable alloy has: A yield strength (0.2% residual strain) of greater than or equal to about 140 ksi (965 MPa); A plastic strain ratio greater than or equal to 0.30; and Failure plastic strain greater than or equal to 8.0%.

16. The nickel-based precipitation hardenable alloy of claim 15, wherein: The titanium is between about 0.8% and about 1.1%, and the iron is between about 16.0% and about 21.0%.

17. The nickel-based precipitation hardenable alloy of claim 15, wherein: The titanium is between about 0.8% and about 1.0%, and the iron is between about 17.0% and 20.0%.

18. The nickel-based precipitation hardenable alloy of claim 15, wherein: The titanium is between about 0.5% and about 0.8%, and the iron is between about 18% and about 21.0%.

19. The nickel-based precipitation hardenable alloy of claim 15, wherein: The yield strength (0.2% residual deformation) is between about 140 ksi (965 MPa) and 170 ksi (1172 MPa).

20. The nickel-based precipitation hardenable alloy of claim 15, wherein: The plastic strain ratio is greater than or equal to 0.35, and the failure plastic strain is greater than or equal to 9.0%.

21. The nickel-based precipitation hardenable alloy of claim 15, wherein: The plastic strain ratio is greater than or equal to 0.45, and the failure plastic strain is greater than or equal to 10.0%.